Counselling on the utilization of agricultural waste as alternative feed for poultry - Dimas Pratidina Puriastuti Hadiani; Tri Ida Wahyu Kustyorini (University of Merdeka Malang, 2023)
Poultry concentrate feed is predominantly produced by animal feed factories in Indonesia. Unfortunately, the selling price of concentrates has been steadily increasing, causing difficulties for poultry farmers in maintaining their businesses. Indonesia, being an agricultural country, possesses a wealth of agricultural products. The abundance of agricultural products, coupled with significant amounts of agricultural waste from by-products, can be processed and utilized as animal feed. In order to address this issue, a service activity was conducted in Suru Village, Doko District, Blitar Regency. The objective was to provide socialization and training on utilizing agricultural waste, which is abundant in Suru Village, as an alternative feed for poultry livestock. The approach employed involved socializing the activities to farmers, addressing the challenges faced by partners, and providing counseling and direct assistance. The counseling sessions focused on the types of agricultural waste readily available in Suru Village that can be utilized in poultry feed, as well as training on formulating simple rations. As a result of this activity, breeders were able to utilize rice bran, an agricultural waste product, as an alternative feed, thereby reducing the cost of expensive commercial feeds. By substituting rice bran in feed formulations for commercial concentrates, farmers were able to save Rp410,000 per 100 kg of purchased feed.